PERGESERAN PARADIGMA MANAJEMEN SUMBER DAYA MANUSIA - Harry Yulianto; Iryani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The role of science or philosophy of science in the development of human resources was very closely related or interdependent. It was because high human resources depend on the thoughts or knowledge possessed by humans. This article aims to critically examine the paradigm shift in Human Resource Management (HRM). The change from the old paradigm to a new paradigm in human resource management will be beneficial for the organization if it was actually practiced in the organization. Several factors experienced a paradigm shift, such as: organizational goals, job design, structure, communication and compensation basis. The paradigm shift in human resource management provides a different focus in carrying out its functions within the organization.